Improving Methodological Approaches to Choosing Strategies and Tactics for the Prevention of Tick-Borne Infections Based on Risk-Oriented Differentiation of Territories at the Municipal Level - D. A. Saveliev; A. I. Blokh; N. V. Rudakov (Проблемы особо опасных инфекций, 2025)
The aim of the work was to improve epidemiological surveillance of tick-borne infections through riskoriented differentiation of territories at the municipal level using new information technologies and GIS technologies. Materials and methods. The work used the data of form No. 2 of the federal statistical surveillance for the period of 2000–2023 in the context of municipalities, obtained from 14 constituent entities of the Russian Federation endemic for three main tick-borne infections (tick-borne viral encephalitis, Ixodidae tick-borne borreliosis, Siberian tick-borne typhus). To calculate risk levels based on average long-term morbidity rates, the computer program “Risk territory: calculation and display of risk territories (as regards infectious morbidity) on the map” developed and patented by the authors and the methodology approved by GOST R ISO 16269-7-2004 were used. Results and discussion. Differentiation of 412 municipalities in 14 constituent entities of the Russian Federation by the levels of risk for the population to contract three tick-borne infections has been carried out. Average long-term indicators of morbidity rates as regards tick-borne infections were calculated, based on the analysis of which threshold values for five risk levels were determined. Classified choropleth cartograms were constructed using the QGIS v.2.18.12 software. Municipalities with different levels of risk for tick-borne viral encephalitis, Ixodidae tick-borne borreliosis and Siberian tick-borne typhus have been identified in the studied constituent entities of the Russian Federation. The results of the study on differentiation of natural-focal areas by the levels of risk of tick-borne infections at the municipal level will allow specialists from the Rospotrebnadzor and healthcare service to more accurately determine the strategy and tactics of anti-epidemic measures.